2015
DOI: 10.1155/2015/753710
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofHelicobacter pylori vacA,cagA, andiceAGenotypes in Cuban Patients with Upper Gastrointestinal Diseases

Abstract: Virulence factors of Helicobacter pylori can predict the development of different gastroduodenal diseases. There are scarce reports in Cuba about H. pylori isolates genotyping. The aim of the present investigation was to identify allelic variation of the virulence genes vacA, cagA, and iceA in sixty-eight patients diagnosed as H. pylori positive by culture. In seven out of 68 patients, strains from both gastric regions were obtained and considered independent. DNA was extracted from all the H. pylori strains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
6
14
2
1
Order By: Relevance
“…Our results were in agreement with Ngoyi et al [35] and lower than Rasheed et al [36]. Feliciano et al [37] reported that during upper endoscopy, patient's mucosa was distributed into non-peptic ulcer dyspepsia in 64.7% and peptic ulcer in 35.3%of cases. Other endoscopic findings (31.7%) were observed among the studied H. pylori infected patients.…”
supporting
confidence: 93%
“…Our results were in agreement with Ngoyi et al [35] and lower than Rasheed et al [36]. Feliciano et al [37] reported that during upper endoscopy, patient's mucosa was distributed into non-peptic ulcer dyspepsia in 64.7% and peptic ulcer in 35.3%of cases. Other endoscopic findings (31.7%) were observed among the studied H. pylori infected patients.…”
supporting
confidence: 93%
“…The results demonstrated a high prevalence of H. pylori virulent genotypes in the Cuban patient population, and the vac As1 allele, cag A gene, and iceA2 allele were the most prevalent (72.0%, 56.0%, and 57.3%, respectively). Alleles from the m‐region showed a similar frequency to s1a and s1b subtypes …”
Section: Prevalence Of Virulence Factors and Associations With Clinicmentioning
confidence: 85%
“…Alleles from the m-region showed a similar frequency to s1a and s1b subtypes. 25 The prevalence of H. pylori as well as non-H. pylori Helicobacters was analyzed in Venezuela by enrolling 71 dyspeptic patients from an urban, and 39 from a rural area. 26 The presence of H. pylori was based on amplification of 16S rRNA, glmM, and ureA genes in 55.0% of patients from urban and 87.2% from rural populations.…”
Section: Prevalence Of Virulence Factors and Associations With Clinmentioning
confidence: 99%
“…Among patients with chronic gastritis, 39.2% were cagA+ (27) . The cagA gene was detected in 42 (56.0%) strains in Cuban patients with upper gastrointestinal diseases (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, further studies may be performed to correlate different digestive disorders with the presence of various virulence factors, including the iceA protein and the different alleles of vacA gen (10) . …”
Section: Discussionmentioning
confidence: 99%